Effect of brominated flame retardants exposure on liver function and the risk of non-alcoholic fatty liver disease in the US population - Xiong Chen; GuoHuang Hu; Bin He; Zhen Cao; JianFeng He; HaiLong Luo; YiJin Li; QianLe Yu (Ecotoxicology and Environmental Safety, 2024)
Background: The relationship between brominated flame retardants (BFRs) exposure and the human liver was still not well understood. Methods: A total of 3108 participants (age > 12) from the National Health and Nutrition Examination Survey (NHANES) database spanning from 2005 to 2016 were included as the study population, with nine BFRs exhibiting a detection rate of over 70% serving as the exposure factor. The singular effects and combined effects of BFRs exposure on liver injury, non-alcoholic fatty liver disease (NAFLD), and advanced hepatic fibrosis (AHF) were evaluated separately. Finally, COX regression was employed to explore the hazard ratios associated with individual BFRs. Results: In our analysis of individual exposures, we found significant positive association of PBB153 with alanine aminotransferase (ALT), PBB153 with aspartate aminotransferase (AST), PBDE47, PBDE85, PBDE99, PBDE100, and PBDE154 with alkaline phosphatase (ALP), PBDE28 and PBB153 with gamma-glutamyl transaminase (GGT), PBB153 with the risk of NAFLD and AHF; and significant negative association of PBB153 with ALP, PBDE28, PBDE47, PBDE99, PBDE100, PBDE85, PBDE209, and PBDE154 with albumin (ALB), PBB153 with AST/ALT. The nonlinear analysis results from Restricted Cubic Spline (RCS) further validated these associations (all P<0.05). In the mixed analysis combining Weighted Quantile Sum (WQS) regression and Quantile G-computation (QGC) analysis, BFRs were positively associated with ALT (β>0, P<0.001), GGT (β>0, P<0.001), and the risk of NAFLD (OR>1, P=0.007). Conversely, BFRs exhibited significant negative correlations with ALP (β<0, P<0.001), ALB (β<0, P<0.001), and AST/ALT (β<0, P<0.001). Furthermore, the COX regression analysis revealed that PBB153 had the highest hazard ratio among the BFRs. Conclusions: BFR exposure may increase the risk of liver injury and NAFLD, with no significant association with AHF risk. The impact of BFR exposure on liver health should not be overlooked, especially in individuals residing in impoverished areas.